The Effect of the Ultra-Micro Economic Empowerment Program On the Well-Being of Coconut Farmers - Lasang, Saharil Salim; Abdullah, Sofyan; Dunggio, Iswan (Gorontalo Development Review, 2025)
This study aims to evaluate the impact of the Ultra Micro Economic Empowerment Program financing on increasing the income of coconut farmers in Avolua Village, to analyze the influence of this program on farmers' access to credit and markets, and to assess the effects of improving the welfare quality of coconut farmers before and after joining the program. The research employed a quantitative approach, with a sample of 50 coconut farmers from Avolua Village. The results indicate that: 1) partially, the area of coconut land and the volume of coconut production have a positive and significant impact on farmers’ income, while production costs have a positive but not significant effect; 2) the PNM Mekaar financing program, access to credit and markets, and the quality of life of coconut farmers collectively influence their level of welfare; and 3) there is a significant improvement in the farmers' quality of life after participating in the financing program.